AB0786 Are We Managing Male Osteoporosis Adequately?. (15th July 2016) - Rogers, M.; Gauci, J.S.; Gauci, J.M.; Azzopardi, M.; Borg, A.
Abstract : Background: Osteoporosis is becoming increasingly recognized as an important public health problem in men, with one in four men over the age of 50 years developing at least one osteoporosis-related fracture in their lifetime. 1 Objectives: The primary aim of our project was to evaluate whether male patients with osteopenia or osteoporosis are being investigated and managed according to the Endocrine Society Guidelines 2 published in June 2012. We also assessed the indications for bone mineral density (BMD) measurements in our cohort. Methods: Patients who had a BMD measurement done at Mater Dei Hospital, Malta, between September and December 2012 were recruited in this study. Information on patient demographics, indication for BMD measurement and other investigations carried out were obtained from the patients' medical notes and iSoft Clinical Manager®. Results: A total of 116 patients had a BMD scan done during the study period. Mean age was 56 years (SD ±15.28). 75.86% (n=88) had at least one documented risk factor for osteoporosis and therefore an indication for BMD measurement. The commonest risk factors were smoking (34.5%), history of long-term corticosteroid use (33.6%) and age above 70 years (18.1%). 49.1% (n=57) had their BMD result recorded in their medical notes. Of these, 24.6% (n=14) were osteoporotic at the hip, and 14.0% (n=8) at the spine. From the cohort of patients with osteoporosis or osteopenia, 40.9% (n=18) had testosterone levels, 27.3% (n=12) had Vitamin D levels, and none had 24-hour urinary calcium levels checked. All patients had a full blood count, calcium, phosphate, renal and liver function tests checked. 77% (n=34) were prescribed calcium supplements and 75% (n=33) also received Vitamin D supplementation. Advice on weight bearing exercise was documented in 22.7% (n=10), whilst advice on smoking cessation was only documented for 12.5% of smoking patients. Of all cases where bisphosphonate therapy was indicated, 55.6% (n=15) were on treatment. 46.7% (n=7) of patients had a dental assessment prior to starting treatment. Conclusions: Our study has identified that a high proportion of BMD scans are being requested in concordance with guidelines. However, a significant number of patients with osteoporosis remain untreated. This stresses the need of increasing awareness amongst clinicians of current guidelines together with improving our patients' education on lifestyle measures and smoking cessation, in order to avoid potential complications which can result in significant morbidity and also mortality. References: National Osteoporosis Foundation. Fast Facts on Osteoporosis. www.nof.org/osteoporosis/diseasefacts.htm . Accessed 29th January 2016. Watts NB, Adler RA, Bilezikian JP, Drake MT, Eastell R, Orwoll ES, Finkelstein JS. Endocrine Society. Osteoporosis in men: an Endocrine Society clinical practice guideline. J Clin Endocrinol Metab. 2012 Jun; 97(6):1802–22. Acknowledgement: Dr Maria Angela Grima, Dr Dillon Mintoff, Dr Malcolm Mintoff, Dr Jessica Spiteri. Disclosure of Interest: None declared